When social phobia meets excessive service: Effects on customer delight and loyalty. (October 2022) - Xiong, Wei; Huang, Meijiao; Okumus, Bendegul; Leung, Xi Yu; Cai, Xiaomei
Abstract: Based on the stress-vulnerability model, this study aims to investigate how social anxiety moderates the customer outcomes of excessive employee effort. Empirical data were collected from 525 respondents. All data were analyzed using PLS-SEM. Our findings indicated that customer delight fully mediated the relationship between excessive employee effort and customer loyalty. Both the negative effects of excessive employee effort on customer delight and customer loyalty were stronger for those high in social anxiety than for those low in social anxiety. The findings provide specific theoretical and practical implications for academics and service operators regarding the implementation of personalized service about delighting customers based on individual heterogeneity and psychological characteristics. Highlights: Excessive employee effort have no direct effect on customer loyalty. Customer delight fully mediated the relationship between excessive employee effort and customer loyalty. Social anxiety is a moderator among excessive employee effort, customer delight and loyalty. Delighting customer should consider customers' heterogeneity in psychological traits.